Tomorrow's people and new technology : changing how we live our lives - Dodds, Felix; Duque Chopitea, Carolina; Ruffins, Ranger (New York, NY : Routledge, 2022)
"As we witness a series of social, political, cultural, and economic changes/disruptions this book examines the Fourth Industrial Revolution and the way emerging technologies are impacting our lives and changing society. The Fourth Industrial Revolution is characterized by the emergence of new technologies that are blurring the boundaries between the physical, the digital, and the biological worlds. This book allows readers to explore how these technologies will impact peoples' lives by 2030. It helps readers to not only better understand the use and implications of emerging technologies, but also to imagine how their individual life will be shaped by them. The book provides an opportunity to see the great potential but also the threats and challenges presented by the emerging technologies of the Fourth Industrial Revolution, posing questions for the reader to think about what future they want. Emerging technologies, such as robotics, artificial intelligence, Big Data and analytics, cloud computing, nanotechnology, biotechnology, the Internet of Things, fifth-generation wireless technologies (5G), and fully autonomous vehicles, among others, will have a significant impact on every aspect of our lives, as such this book looks at their potential impact in the entire spectrum of daily life, including home life, travel, education and work, health, entertainment and social life. Providing an indication of what the world might look like in 2030, this book is essential reading for students, scholars, professionals, and policymakers interested in the nexus between emerging technologies and sustainable development, politics and society, and global governance"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial revolution -- History -- 21st century; Sustainable development -- History -- 21st century; Environmental policy; Economic policy; Social change; BUSINESS & ECONOMICS / Development / Sustainable Development; NATURE / Ecology; POLITICAL SCIENCE / Public Policy / Economic Policy